Fault-tolerant dissipative preparation of atomic quantum registers with fermions - Griessner, A; Daley, A; Jaksch, D; Zoller, P (American Physical Society, 2005)
We propose a fault-tolerant loading scheme to produce an array of fermions in an optical lattice of the high fidelity required for applications in quantum-information processing and the modeling of strongly correlated systems. A cold reservoir of fermions plays a dual role as a source of atoms to be loaded into the lattice via a Raman process and as a heat bath for sympathetic cooling of lattice atoms. Atoms are initially transferred into an excited motional state in each lattice site and then decay to the motional ground state, creating particle-hole pairs in the reservoir. Atoms transferred into the ground motional level are no longer coupled back to the reservoir, and doubly occupied sites in the motional ground state are prevented by Pauli blocking. This scheme has strong conceptual connections with optical pumping and can be extended to load high-fidelity patterns of atoms.